Derivative Trading in Indian Stock Market: Investor’s Perception - Choksi, Anjali (Indian Journal of Finance, 2010)
The most significant event in finance during the past decade has been the astonishing development and expansion of financial derivatives. These instruments enhance the ability to differentiate risk and allocate it to those investors who are most able and willing to take it-a process that has undoubtedly improved national productivity, growth and standards of living.